Making Britain the best place in the world to work: how to protect and enhance workers' rights after Brexit … and coronavirus - Keith Sisson (University of Warwick, Industrial Relations Research Unit, 2020)
The UK government's promise in the Queen's Speech of 19 December 2019 to protect and enhance worker's rights after Brexit has taken on new urgency in the light of the coronavirus pandemic, the inadequacy of the present framework being exposed for all to see. Issues highlighted include the social safety net, anytime/anywhere working, employment status and, above all, the low pay and insecurity of many of the 'key' workers society depends on for everyday services. A Ministry for Employment and Social Affairs and a specialist social partnership body like the Low Pay Commission are needed to ensure that worker's rights are regularly reviewed and updated to reflect changing circumstances. Effective enforcement mechanisms are a must, which means a well-funded enforcement agency and requiring businesses to take responsibility for what happens in their supply chains, with provisions for social licensing as well as mandatory due diligence. The government also needs to improve the evidence base for decision making about workers' rights including a regular survey of management policies and practices based on the internationally renowned Workplace Employment Relations Survey. Overall, the task will make sense to more people if the government uses the language of 'fairness'.
Keywords: 330; employee protection; Brexit; coronavirus; Great Britain; Arbeitnehmerschutz; Reform; Brexit; Coronavirus; Großbritannien